USE OF SGLT2 INHIBITOR IN ALPELISIB-INDUCED HYPERGLYCAEMIA - Nordin, Hidayatil Alimi Bin Keya; Jeevaraj, Lavanya; Rahmatullah, Ijaz Bt Hallaj (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION/BACKGROUND Hormone receptor-positive (HR+) and human epidermal growth factor receptor 2-negative (HER2-) breast cancer constitutes the most common form of breast cancer. Forty percent of patients with HR+/HER2- breast cancer have mutations in phosphatidylinositol-4,5-bisphosphate 3-kinase catalytic subunit alpha, which induce hyperactivation of phosphatidylinositol 3-kinase (PI3K) contributing to resistance to endocrine therapy. The use of PI3K inhibitor (alpelisib) in combination with fulvestrant has been approved for the treatment of postmenopausal women with HR+/HER2-, PIK3CA- mutated advanced breast cancer. Hyperglycemia is the most common side effect of Alpelisib. CASE We describe a 54-year-old female with diabetes who developed uncontrolled hyperglycaemia after initiation of Alpelisib despite taking Vildagliptin and basal-bolus insulin (total daily dose: 52 units per day). Before alpelisib initiation, this patient had good glycaemic control with HbA1c of 6.7% while on Metformin 500 mg BD. Her oncologist discontinued Metformin and started the patient on Vildagliptin 50 mg OD due to renal impairment. Her blood glucose levels (monitored by a continuous glucose monitoring device) significantly worsened once alpelisib was started. On day 1 of treatment, her sugar increased tomore than 10 mmol/L, thus basal-bolus insulin was started. Despite basal-bolus insulin (S/C Glulisine 12 units TDS, S/C Insulatard 16 units ON), her glucose remained in the range of 10 to 17 mmol/L. Empagliflozin was started on day 8 of Alpelisib treatment. With Empagliflozin, blood glucose levels improved, ranging between 6 to 10 mmol/L, and we were able to discontinue insulin therapy. CONCLUSION We report the successful management of alpelisib-induced hyperglycaemia with the use of SGLT-2 inhibitor.